Maternal depression and breastfeeding in home visitation. (December 2020) - Scheiber, Francesca A.; Segre, Lisa S.; O'Hara, Michael W.; Taylor, Darby; Brock, Rebecca L.
Highlights: Women in this study were less depressed than women in other home visiting studies. Rates of breastfeeding in this study were higher than in the general population. Non-Hispanic White mothers were less likely to breastfeed than other groups. Prenatal depression scores did not predict breastfeeding at 3 months postpartum. Postpartum depression scores predicted breastfeeding at 3 months postpartum. Abstract: Background: Home visitation is a popular mechanism for supporting parents and their young children. Breastfeeding is often promoted by home visitors due to its health benefits. However, maternal depression may interfere with breastfeeding. Thus, home visitors may be attempting to encourage health-promoting behaviors like breastfeeding, but maternal depression may interfere with engagement in those behaviors. Method: The data for this study were provided by the Des Moines Healthy Start and the Empowerment Family Support Project (DMHSP). We analyzed the relation between depression and breastfeeding for 364 women. Results: First, rates of elevated depression scores in this sample of women (8.7%-21.4% of women) were lower than rates of elevated depression scores reported in other studies of women enrolled in home visitation (30%–50% of women). Second, rates of breastfeeding at 3 months postpartum in this sample (56% of women) were higher than rates of breastfeeding reported in the general population (51% of women). Third, Non-Hispanic White women were significantly less likely to breastfeed compared to other racial groups. Fourth, average Edinburgh Postnatal Depression Scale (EPDS) scores during the first 3 months postpartum, but not during pregnancy, were predictive of likelihood to breastfeed at 3 months postpartum, even after accounting for demographic characteristics. Conclusion: Addressing maternal depression during the early postpartum period may increase the likelihood of engaging in breastfeeding.